Challenges for Creating Visibility of European Cultural Heritage. A Case Study of the European Heritage Label - Čeginskas, Viktorija L.A (Ethnologia Fennica, 2019)
The European Heritage Label (EHL) is a recent flagship heritage action of the European Union and focuses on the European dimension of Europe’s histo- ry and heritage as part of the Union’s cultural policy. One of the central con- cerns of the EU’s cultural policy is to generate a sense of belonging and iden- tity among European citizens. While efficient promotion of the visibility of the EHL among European audiences could be expected corresponding to the political objectives, the EHL continues to struggle with broader public recog- nition. Based on fieldwork findings, the article discusses the visibility of the EHL action as a network of heritage sites that challenges national narratives by promoting a European dimension of heritage. The article identifies diverse shortcomings in creating public visibility, such as the missed opportunity of the European Year of Cultural Heritage 2018 for creating useful synergies. The findings suggest that the EHL has potential to initiate public debate of what is European heritage, which may result in enhancing social cohesion in Europe. However, the label would benefit from the development of a joint strategy for improving the visibility of the EHL network at the local, nation- al and European levels.
Keywords: European cultural heritage; visibility; European Heritage Label; European Year of Cultural Heritage